One moment estimate for the supremum of normalized sums in the law of the iterated logarithm - Matsak, I. K.; Plichko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For a sequence of independent random elements in a Banach space, we obtain an upper bound for moments of the supremum of normalized sums in the law of the iterated logarithm by using an estimate for moments in the law of large numbers. An example of their application to the law of the iterated logarithm in Banach lattices is given.